GH, IGF-I and IGFBP-3 responses to maximal rowing exercise in male rowers - Ding, N.; Jiang, W.; Tang, Q.; Dai, X.; Ji, S. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The aim of this study was to investigate the effect of 2000m exhausting rowing ergometer exercise (lasting about 7 min) on serum GH, IGF-I and IGFBP-3 in male rowers.